2015
DOI: 10.1108/jme-03-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and functional diversity in the elementary classroom: strategies for teachers

Abstract: Purpose – This paper aims to discuss current issues and provide suggestions for solutions. Today’s classrooms across schools in the USA are increasingly diverse. This diversity encompasses students from a myriad of cultural and linguistic and backgrounds’ academic performance levels. Teacher training programs and schools are making efforts to enhance teacher knowledge in regards to this cultural and functional diversity. Problems continue to exist because it is challenging to clearly perceive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
5
1
1
Order By: Relevance
“…A teacher is not only required to have the competence to teach language and literature, but is also required to bridge the differences between students of different cultures. This is as said (Cousik 2015), in his research. According to him, there is a need for systemic efforts that encourage ongoing debate over cultural and functional diversity, increase teachers' knowledge in the field of best practices in teaching children from diverse cultural and functional backgrounds that foster collaboration between schools and families.…”
Section: The Role Of Government and Teachers In The Application Of Intertextuality Studies In Literature In Multicultural Educationsupporting
confidence: 76%
“…A teacher is not only required to have the competence to teach language and literature, but is also required to bridge the differences between students of different cultures. This is as said (Cousik 2015), in his research. According to him, there is a need for systemic efforts that encourage ongoing debate over cultural and functional diversity, increase teachers' knowledge in the field of best practices in teaching children from diverse cultural and functional backgrounds that foster collaboration between schools and families.…”
Section: The Role Of Government and Teachers In The Application Of Intertextuality Studies In Literature In Multicultural Educationsupporting
confidence: 76%
“…The study findings showed that CQ of principals significantly influenced Latino students' achievement levels in both math and language arts only in eighth grade. No significant influence of teachers' CQ on student achievement on any of the three grade levels was particularly contrary to the expectations portrayed in the relevant literature (Cousik, 2015;Garza, 2009;Gay, 2000).…”
contrasting
confidence: 72%
“…The California Department of Education Educational Demographics Unit (2013) stated that 71 per cent of all students in K-12 schools were ethnic minorities, while only 29 per cent of teachers are of an ethnic background. A classroom that has students from culturally diverse backgrounds holds plenty of opportunities for teachers and students to learn distinct viewpoints from one another, acquire understanding and encourage cross-cultural tolerance (Cousik, 2015). Although it is important to intertwine multicultural education into teacher-credentialing programs, it is the students who matter most.…”
Section: Introductionmentioning
confidence: 99%